A Linguistic and Rhetorical Study of Collocation in Shahnameh - Maryam Tafaroji Yeganeh; Qmars Niksersht (مطالعات زبانی و بلاغی)
One of the conceptual relations between words is collocation which means two or more words are collocated in such a way that the possibility of their coming together is predictable. In literary language, collocation is the result of mental association and linguistic connections between parts of speech. Persian poetry regarding harmony in the different dimensions of speech, always has been distinct and this feature exists in Ferdowsi`s poem too. This facts lead us to look for finding the answers for the questions like, does collocations applied in Shahname, if it is used what kinds of it and to what extent are they used? This research is a kind of descriptive, corpus-based one, which has been done based on Safavi’s semantics fields theory which is based on structural linguistics. The corpus of study includes 1060 verses of Shahame. The results indicate that  The application of all kinds of lexical collocations such as noun + noun , noun + adjective and noun + verb and associative collocation such as semantic association , phonetic association and syntactic and structural association and the existence of proportion and wide connections in conceptual relations network like hyponymy , polysemy , synonymy and semantic opposition applied in shahnameh can be of the most important and most high frequency coordinates of linguistic and literary level of Ferdowsi`s poem .